Electrical Diseases of the Heart 2013
DOI: 10.1007/978-1-4471-4978-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia

Abstract: Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is characterized by the patchy replacement of myocardium by fatty or fibrofatty tissue. These changes lead to structural abnormalities including right ventricular enlargement and wall motion abnormalities that can be detected by echocardiography, angiography, and cine MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…ARVD/C is an uncommon but important cause of SCD because most of these individuals are young. It is estimated that it accounts for one fifth of all episodes of SCD that occur in patients younger than the age of 35 years (13). During the past decade, 4 studies, predominantly in patients with sustained VT/VF, have demonstrated the efficacy of ICD therapy and its impact on SCD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…ARVD/C is an uncommon but important cause of SCD because most of these individuals are young. It is estimated that it accounts for one fifth of all episodes of SCD that occur in patients younger than the age of 35 years (13). During the past decade, 4 studies, predominantly in patients with sustained VT/VF, have demonstrated the efficacy of ICD therapy and its impact on SCD prevention.…”
Section: Discussionmentioning
confidence: 99%